Multiple Heterojunction System of Boron Nitride‐Graphene/Black Phosphorene as Highly Efficient Solar Cell. Issue 9 (8th August 2021) - Zeng, Jian; Xu, Liang; Dong, Kejun; Yang, Kai; Wang, Ling‐Ling
Abstract: Excitonic solar cell (XSC) based on 2D materials has attracted widespread attention. Using first‐principles calculations, XSC with high theoretical power conversion efficiency of around 21.3% formed by the combination of 2D cross‐linked hexagonal boron nitride‐graphene (BN‐GR) and black phosphorene (BP) is rationally designed in this work. The good visible‐light response, small conduction band offset, as well as the suitable band‐gap (1.41 eV) of electron donor (BN‐GR) lay the foundation for the excellent photoelectric conversion performance of the BN‐GR/BP heterojunction. More importantly, it is found that the substrate (BN‐GR) with different composition can drive uneven interlayer charge transfer in the BN‐GR/BP heterojunction, resulting in the formation of an obvious electron–hole puddle at the heterojunction interface. This forms a lateral discharge functional optoelectronic device in addition to the vertical direction, which may even be a new development direction for electronic energy storage devices in the future. Abstract : Excitonic solar cell with high theoretical power conversion efficiency of around 21.3% formed by the combination of 2D cross‐linked boron nitride‐graphene (BN‐GR) and black phosphorene (BP) is rationally designed in this work. This forms a lateral discharge functional optoelectronic device in addition to the vertical direction, which may even be a new development direction for electronic energy storage devices in the future.